Proceso de atención nutricional en paciente masculino con virus de inmunodeficiencia humana y desnutrición crónica. - Aguirre Vásquez, Juan Andrés (2024)
The Human Immunodeficiency Virus (HIV) is a chronic disease that compromises the immune system, posing a significant public health challenge. In Ecuador, the prevalence of HIV has increased, with over 39,000 people living with the disease according to the Ministry of Public Health in 2023. The World Health Organization (WHO) emphasizes that proper nutrition is crucial for enhancing the effectiveness of antiretroviral therapy (ART) and preventing complications. This study aimed to develop a nutritional care process for a 40-year-old male patient with HIV and chronic malnutrition. The presumptive diagnosis was HIV-associated cachexia, while the definitive diagnosis was HIV disease. Dietary analysis revealed poor nutrition, contributing to weight loss and anemia. Severe malnutrition was diagnosed through clinical, anthropometric, and dietary evaluations, leading to a proposed intervention involving a hypercaloric, high-protein diet of 2000 kcal, supplemented with enteral support. The treatment included monthly follow-ups for three months, resulting in significant improvements in anthropometric and biochemical indicators, such as weight gain, BMI, and hemoglobin and hematocrit levels. These findings underscore the importance of nutritional support in the recovery of HIV patients, enhancing their overall condition and preventing additional complications.